Green Transformation: Orchestrating Creative Economy To Revitalize The Potential of Bangka Belitung - Ferry Bakti; Burham Isnanto; Amri , Amri; Jack Saputra (Jurnal Multidisiplin Indonesia, 2025)
The development of a sustainable creative economy in Bangka Belitung represents a complex exploration of economic transformation, investigating the critical interplay between green capabilities, digital readiness, external support, and sustainability awareness through an innovative quantitative research approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). By analyzing data from 357 creative entrepreneurs through an online survey conducted in November-December 2023, the study employs a 5-point Likert scale to examine environmentally friendly production practices, digital platform benefits, training access, and environmental understanding, revealing that external support and sustainability awareness have the most significant influence on green business performance with path coefficients of 0.751 and 0.761, respectively. The research addresses significant gaps in previous literature by developing a unique theoretical framework that connects green capabilities with digital readiness in the local creative economy context, ultimately explaining 78.4% of variation in green business performance and 78.6% in business sustainability. The findings confirm the critical importance of integrating organizational resources and unique capabilities to achieve sustainable competitive advantage, providing substantial theoretical contributions to the creative and green economy while offering practical recommendations for local governments, educational institutions, and business actors to develop targeted training programs, curricula, and strategies that support green economic transformation.